2004
DOI: 10.1242/jcs.01368
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin ligase Rad18Sc localizes to the XY body and to other chromosomal regions that are unpaired and transcriptionally silenced during male meiotic prophase

Abstract: SummaryUbiquitin ligase Rad18 Sc localizes to the XY body and to other chromosomal regions that are unpaired and transcriptionally silenced during male meiotic prophase

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 56 publications
(67 reference statements)
1
42
0
Order By: Relevance
“…HR6A and HR6B show 96% amino acid similarity, and at present we have no indications that HR6A and HR6B perform different activities, either in somatic or in germline cells. In spermatocytes, HR6B localizes mainly on the XY body, together with the putative partner ubiquitin ligase RAD18 (van der Laan et al, 2004). Although H2A K119ub1 is also enriched on the XY body, our findings indicate that HR6B activity is not responsible for this modification.…”
Section: H2a T120ph and Regulation Of Chromatin Organizationmentioning
confidence: 54%
See 1 more Smart Citation
“…HR6A and HR6B show 96% amino acid similarity, and at present we have no indications that HR6A and HR6B perform different activities, either in somatic or in germline cells. In spermatocytes, HR6B localizes mainly on the XY body, together with the putative partner ubiquitin ligase RAD18 (van der Laan et al, 2004). Although H2A K119ub1 is also enriched on the XY body, our findings indicate that HR6B activity is not responsible for this modification.…”
Section: H2a T120ph and Regulation Of Chromatin Organizationmentioning
confidence: 54%
“…In particular, recruitment of the checkpoint kinase ATR by the BRCA1 protein and subsequent phosphorylation of Ser139 of H2AX have been shown to be essential for MSUC (Fernandez-Capetillo et al, 2003;Turner et al, 2004;Turner et al, 2005). Interestingly, H2A K119ub1 is also enriched on the XY body, concomitant with accumulation of the HR6B enzyme van der Laan et al, 2004). However, HR6A-or HR6B-dependent histone modifications in mammalian cells have not been described.…”
Section: Introductionmentioning
confidence: 99%
“…Sc (as described by van der Laan et al [53]), rabbit polyclonal antiubiquitin (DakoCytomation, Glostrup, Denmark), rabbit polyclonal anti-trimethylated H3 lysine 9 (Upstate), rabbit polyclonal anti-Hr6a/b (1:100) (described by van der Laan et al [53]), and rabbit polyclonal anti-␄-H2AX (Upstate). For polyclonal primary antibodies, the secondary antibodies were fluorescein isothiocyanate (Sigma, St. Louis, Mo.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, specific nonhistone proteins, histone variants (summarized in Fig. 2) and chemically modified histones (by phosphorylation, acetylation, methylation, or ubiquitination; Hoyer-Fender et al, 2000;Khalil et al, 2004;van der Laan et al, 2004) can be found in the condensed XY pair. Some of these proteins may have a direct effect on chromatin condensation; others may contribute to the structure of the unsynapsed axial cores, which undergoes splitting and bulging during meiotic prophase; other proteins may regulate the occurrence of the PAR and eventually the completion of meiotic prophase.…”
Section: The C-terminus Of Scp3 and Xmr Displaysmentioning
confidence: 99%